Complexity and The Experience of Managing in Public Sector Organizations (Routledge, 2006)
A fundamental problem of public sector governance relates to the very way of thinking it reflects; where organization is thought of as a ‘thing’, a system designed to deliver what its designers choose. This volume questions that way of thinking and takes a perspective in which organizations are complex responsive processes of relating between people.